2018
DOI: 10.1371/journal.pbio.3000069
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell copy number variant detection reveals the dynamics and diversity of adaptation

Abstract: Copy number variants (CNVs) are a pervasive source of genetic variation and evolutionary potential, but the dynamics and diversity of CNVs within evolving populations remain unclear. Long-term evolution experiments in chemostats provide an ideal system for studying the molecular processes underlying CNV formation and the temporal dynamics with which they are generated, selected, and maintained. Here, we developed a fluorescent CNV reporter to detect de novo gene amplifications and deletions in individual cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(158 citation statements)
references
References 105 publications
6
145
0
Order By: Relevance
“…In cancer cells, for instance, aneuploidy is known to result in deregulation of the transcriptome and proteome (Dürrbaum & Storchová, ; Ried et al, ). Aneuploidy, as with any other alteration in gene copy number (Lauer et al, ), can result in differential gene expression (Sheltzer, Torres, Dunham, & Amon, ). Under certain conditions, such changes in gene dosage may provide fitness benefits to the cell that outweigh the costs of maintaining the aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer cells, for instance, aneuploidy is known to result in deregulation of the transcriptome and proteome (Dürrbaum & Storchová, ; Ried et al, ). Aneuploidy, as with any other alteration in gene copy number (Lauer et al, ), can result in differential gene expression (Sheltzer, Torres, Dunham, & Amon, ). Under certain conditions, such changes in gene dosage may provide fitness benefits to the cell that outweigh the costs of maintaining the aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency with which aneuploid cells are recovered following the exposure of yeasts to stress in the laboratory suggests that it can serve as an adaptation mechanism to harsh environments (see Box 1 and Table 1 for more detailed information). In S. cerevisiae, adaptation though aneuploidy is likely due to the amplified or modified expression of genes on aneuploid chromosomes, which can lead to increased tolerance to environmental stress (Chen et al, 2012;Lauer et al, 2018;Linder, Greco, Seidl, Matsui, & Ehrenreich, 2017;Millet, Ausiannikava, Le Bihan, Granneman, & Makovets, 2015;Selmecki et al, 2015;Yona et al, 2012). This includes low nutrient availability (Gresham et al, 2008;Hong & Gresham, 2014;Selmecki et al, 2015;Sunshine et al, 2015), high ethanol concentrations (Voordeckers et al, 2015), high temperature ( Figure 2 adapted from Yona et al, 2012), and telomerase insufficiency (Millet et al, 2015).…”
Section: Aneuploidy In Laboratory Strainsmentioning
confidence: 99%
“…Re-integration of eccDNA provides an efficient pathway for gene amplification, with various chromosomal adaptations in lower eukaryotes being known or predicted to have emerged through eccDNA intermediates [14][15][16][17][18]. In tumour cells, aggregation of smaller eccDNA to large (1-5MB), microscopically visible double minutes, and re-integration in homogeneously staining regions to yield high-copy chromosomal repeats has also been reported [7,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These dual markers ensured the reporter plasmid could be initially introduced and be retained in plasmid-lacking strains. In addition the GFP allows strains to be easily quantified for plasmid presence, absence, and copy number that scales with GFP intensity in yeast [63][64][65][66] . Our analyses revealed that GFP intensity for this 2µ reporter plasmid is roughly normally distributed across single cells (Supplementary Figure S1) indicating that GFP signal did not saturate the detector at high copy number.…”
Section: Scampr: a Single-cell Assay For Measuring Plasmid Retentionmentioning
confidence: 99%